Training on Making Cashew Chocolate Bars as One of the Developing Creativity in Business Ideas from an Early Age for Children at SDN 1 Pelem, Jatisrono District, Wonogiri: Pelatihan Pembuatan Cokelat Batang Mete sebagai Salah Satu Pengembangan Kreativitas Ide Berbisnis Sejak Dini bagi Anak-anak di SDN 1 Pelem, Kecamatan Jatisrono, Wonogiri - Richardo, Kelvin Matthew; Husnun, Fadilah; Astuti, Nuri (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2025)
Jatisrono District, located in Wonogiri Regency, Central Java, is one of the regions with a significant number of cashew nut MSMEs (Micro, Small, and Medium Enterprises). The majority of cashew nut products sold are simple processed goods. With the intent to transform cashew nuts into innovative products for sale and to enhance early awareness about business skills, the FATIPA UNISRI community service program organized a training workshop on making cashew chocolate as a business idea for students at SDN 1 Pelem. This event, held in August 2024, aimed to motivate students to develop innovative business concepts to improve their personal economic prospects. The outcome of the program demonstrated that participants easily grasped the basic concepts of small-scale business, learned how to create attractive and appropriate packaging, and expressed their creativity in crafting chocolate according to their preferences.